Kampanye Politik melalui Media Sosial pada Pemilu Legisatif 2014 di Kota Pekalongan - Rusda, Aisya; Ngabiyanto, Ngabiyanto; Munandar, Moh. Aris (Universitas Negeri Semarang, 2017)
Election have relationship to close with political campaign. In 2014 legislative election, political campaign not only did with face to face system expect for began to use a new tool such as trough with social media. In the Pekalongan city, some people make use of social media via gadget smartphone as well as computer. So campaign via social media capable embed influence in Pekalongan city. Issues who examine in this research: (1) How implementation political campaign with social media on legislative election 2014 in Pekalongan city. (2) How effectivity political campaign with social media on legislative election 2014 in Pekalongan city. (3) What support factor and resistor political campaign with social media on legislative election 2014 in Pekalongan city. The purpose of research is to be know implementation of political campaign with social media on legislative election 2014 in Pekalongan city. Method of research is qualitative. Sorting data with interview and documentation. Legality testing data with trianggulasi technique. Result in this research are as follow; (1) Implementation political campaign with social media on legislative election 2014 in Pekalongan city are did with some candidate with kind social media Facebook and YouTube. a campaign message to be delivered on posts with form submission vision and mission ideas and program ideas, activity photo and politic issue who then forming an image. (2) Effectivity campaign with social media on legislative election 2014 in Pekalongan city ablity of candidate only extent interesting a user social media but not to be effective with affecting publicly listed the candidates. (3) Factor booster politic campaign with social media on legislative election 2014 in Pekalongan city is: a) gadget and internet, b) the ablity a candidate with using social media, and c) bearer of political party.